2011
DOI: 10.1063/1.3647111
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of the Compton Form Factor H from DVCS Measurements in the Quark Sector

Abstract: Abstract. Working at twist 2 accuracy and assuming the dominance of the Generalized Parton Distribution H we study the helicity-dependent and independent cross sections measured in Hall A, the beam spin asymmetries measured in Hall B at Jefferson Laboratory and beam charge, beam spin and target spin asymmetries measured by Hermes. We extract the real and imaginary parts of the Compton Form Factor H , the latter being obtained with a 20-50 % uncertainty. We pay extra attention to the estimation of systematic er… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 64 publications
(119 reference statements)
2
20
0
Order By: Relevance
“…The future JLab-12 GeV and COMPASS-II program will provide soon bunches of data, giving a hope to get access to GPDs with a high degree of precision. There are indeed now intense activities [28][29][30][31] to move from discovery era to precision physics.…”
Section: Jhep10(2012)049mentioning
confidence: 99%
“…The future JLab-12 GeV and COMPASS-II program will provide soon bunches of data, giving a hope to get access to GPDs with a high degree of precision. There are indeed now intense activities [28][29][30][31] to move from discovery era to precision physics.…”
Section: Jhep10(2012)049mentioning
confidence: 99%
“…The problem is critical, in particular, for both higher ζ values and for the real CFFs. Furthermore, the analysis of [17] does obtain model independent extractions of CFFs at the expense of not allowing for extrapolations to kinematical domains beyond the very sparse data sets.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15]). A pragmatic response was given in [16,17] where an assessment was made of which GPDs can be extracted using the present body of data from Jefferson Lab and Hermes. In particular, it was concluded that the only CFFs that are presently constrained by experiments are ReH and ImH, with rather large errors, up to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Global fitting is still at an early stage (see however Ref. [50,51,59]). The analysis of deeply virtual exclusive experiments presents in fact an increased level of complication because GPDs are complex amplitudes (four chiral even and four chiral odd) embedded in the CFFs.…”
Section: Pos(dis 2010)018mentioning
confidence: 99%
“…This observable is sensitive to the real part of the DVCS scattering amplitude. The first global analyses of DVCS data have started (e. g. [50,51]). Their aim is to extract in a model-independent way the real and imaginary parts of CFFs.…”
Section: Pos(dis 2010)018mentioning
confidence: 99%